2007
DOI: 10.1161/01.atv.0000282193.31936.fd
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Exposure to Maternal Atherosclerotic Risk Factors Increases the Susceptibility to Atherosclerosis in Adult Life

Abstract: Objective-Maternal hypercholesterolemia is associated with a higher incidence and faster progression of atherosclerotic lesions in neonatal offspring. We aimed to determine whether an in utero environment exposing a fetus to maternal hypercholesterolemia and associated risk factors can prime the murine vessel wall to accelerated development of cardiovascular disease in adult life. Methods and Results-To investigate the epigenetic effect in utero, we generated genetically identical heterozygous apolipoprotein E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 35 publications
(27 reference statements)
2
59
0
Order By: Relevance
“…59 The possibility that maternal risk factors play a role in aneurysmal disease has received little attention. In view of evidence that in utero factors can program arterial gene expression in later life, regional differences in hemodynamic conditions could have a similar effect.…”
Section: Vascular Elastogenesismentioning
confidence: 99%
“…59 The possibility that maternal risk factors play a role in aneurysmal disease has received little attention. In view of evidence that in utero factors can program arterial gene expression in later life, regional differences in hemodynamic conditions could have a similar effect.…”
Section: Vascular Elastogenesismentioning
confidence: 99%
“…21 Moreover, plaque formation was increased in offspring born to hypercholesterolemic dams. 14,21 In a human study, the effects of exposure to diabetes in utero were evaluated in the macrosomic offspring of both diabetic and healthy mothers. The diabetic mothers had significantly higher total and LDL-C levels (219.8 versus 146.5 mg/dL) compared with the healthy mothers, and their macrosomic offspring had significantly higher LDL-C levels than macrosomic neonates of healthy mothers (126.1 versus 74.2 mg/dL).…”
Section: Discussionmentioning
confidence: 99%
“…11 There are also indications that, besides hyperglycemia, maternal hypercholesterolemia may increase the risk for CVD in the offspring. [12][13][14][15] A recent study showed that adult mice born to hypercholesterolemic dams had an increased transcriptional activity of both genes involved in the cholesterol synthesis and LDLR in the liver. 15 In humans, fatty streak formation progressed strikingly faster in children of hypercholesterolemic mothers than in those of normocholesterolaemic mothers, 16 but the longterm consequences in humans are still controversial.…”
mentioning
confidence: 99%
“…Intrauterine exposure to maternal atherosclerotic risk factors may increases the susceptibility to atherosclerosis in adult life (Alkemade et al, 2007). In a morphometric postmortem analysis of atherosclerosis in fetuses and children (Fate of Early Lesions in Children Study), it is demonstrated that specifically maternal hypercholesterolemia is associated with a higher incidence of atherosclerotic lesions during the fetal period and a faster progression of these atherosclerotic lesions after birth even under conditions of normocholesterolemia in the offspring (Napoli et al, 1999).…”
Section: Vascular Dysfunction In Children Of Women With Prlmentioning
confidence: 99%